Multi-Parameter Characterization of Disease-Suppressive Bio-composts from Aromatic Plant Residues Evaluated for Garden Cress (Lepidium sativum L.) Cultivation - Catello Pane; Riccardo Spaccini; Michele Caputo; Enrica De Falco; Massimo Zaccardelli (Horticulturae, 2022)
Garden cress is a vegetable crop in the Brassicaceae family that is appreciated for its nutraceutical and taste-giving components in minimally processed food chains. Due to its very short cycle, which depends on the range of production from microgreens to baby-leaf vegetables, this crop is threatened by soil-borne pathologies developing within the initial stages of germination and emergence. This study aims to evaluate the suppressive bio-compost as an innovative means to counteract the main telluric diseases of garden cress and reduce the risks of yield loss by adopting sustainable remedies and decreasing the dependence on synthetic fungicides. Therefore, eleven green composts obtained using both previously distilled and raw aromatic plant residues were analyzed for suppressive properties against Rhizoctonia solani and Sclerotinia sclerotiorum on sown garden cress. The biological active component of the composts, detected by CO2-release, FDA-hydrolysis and microbial counts, proved to be indispensable for pathogen control in vitro and in vivo, as demonstrated by the loss of suppressiveness after sterilization. Cross-polarization magic angle spinning 13C-nuclear magnetic resonance (CP-MAS-13C-NMR) was used to analyze the molecular distribution of organic C in composts. The results indicated the suitability of the feedstock used to make quality compost. The suppression levels shown by composts P1 (40% wood chips, 30% escarole and 30% a mixture of sage, basil, mint and parsley) and P2 (40% wood chips, 30% escarole and 30% a mixture of essential oil-free sage, basil and rosemary) are promising for the sustainable, non-chemical production of garden cress vegetables.